Covid-19 and lockdowns make differences clearer - Hasan, Md. Mahmudul (2020)
Covid-19 has affected human life and livelihoods around the world. The impact of it on people varies greatly depending on their circumstances and considering the symptoms they experience. Accordingly, their responses to the pandemic have been diverse and multifaceted. While most people have found themselves unprepared and floundering during the lockdown period, those who are well developed mentally and intellectually have made the best of it. Covid-19 has helped define our abilities and ourselves.